Pengaruh Teknik Relaksasi Benson Terhadap Penurunan Intensitas Nyeri Pada Pasien Post Kemoradiasi Kanker Nasofaring Di Ruangan Onkologi Rumah Sakit Murni Teguh - Pangaribuan, Firiska; Sagala, Lam Murni (Indonesian Trust Nursing Journal, 2025)
Pain is a unique, complicated, universal and individual sensation experienced by post chemoradiation patients with nasopharyngeal cancer. One of the non-pharmacological techniques that can reduce pain intensity is the Benson relaxation technique. The objective of this study is to determine the effect of Benson relaxation techniques on reducing pain intensity in post chemoradiation patients with nasopharyngeal cancer. This research method was a quasi-experimental study using a one-group pretest and posttest design. The research was conducted in the Oncology Room at Murni Teguh Hospital Medan. The total population was 36 people and all of them were sampled. The analysis was performed univariate and bivariate using paired sample t-test with a confidence level of 95% (a = 0.05). The results of this study indicated that the pain intensity of post chemoradiation patients with nasopharyngeal cancer before being given Benson relaxation technique intervention (pretest) was in the moderate pain category (94.4%). After being given Benson relaxation technique intervention (posttest) in the category of mild pain (83.3%). The Benson relaxation technique has an effect on reducing the pain intensity of post chemoradiation patients with nasopharyngeal cancer or there is a difference in pain intensity before and after being treated with the Benson relaxation technique (pretest-posttest) at Teguh Pure Hospital Medan, p-value = 0.000 and t value = 24.612. It is concluded that Benson relaxation technique is effective to reduce pain intensity in post chemoradiation patients with nasopharyngeal cancer. It is recommended that the leadership of Murni Teguh Medan Hospital make a policy by making SOP for Benson relaxation techniques so that every post chemoradiation patient with nasopharyngeal cancer receives non-pharmacological Benson relaxation techniques.